Hormone Replacement Therapy: Lebanese Women’s Awareness, Perception, and Acceptance - A. Anastasia Salame; Mohammad J. Jaffal; Fatin Khalifeh; Dalia Khalife; Ghina Ghazeeri (Obstetrics and Gynecology International)
Objectives. Hormone replacement therapy (HRT) had been the gold standard for the treatment of menopausal symptoms until the publication of the World Health Initiative (WHI) study. After the WHI study, the use of HRT changed among the physicians and patients all over the world despite newer more reassuring data. This study aimed to investigate the knowledge and attitudes of women towards HRT and the factors affecting it for better counseling. Study design. A clinic-based cross-sectional study using a survey was offered to women aged 40 years and above coming to the women’s health center at the American University of Beirut Medical Center (AUBMC) from October 1st, 2017, till March 31st, 2018. The questionnaire included questions about demographics and menopausal symptoms in addition to knowledge and attitudes towards menopause and HRT. Main outcome measures. Our main hypothesis was that women would be aware of HRT as a treatment modality; however, the majority would have a negative attitude towards its usage. Results. The response rate was 87.8%. Seventy-three percent of the respondents had already heard about HRT with 57.9% supporting the use of HRT; however, 47.9% did not know when to use it. The significant predictor for having heard about HRT and a positive attitude towards HRT were having HRT prescribed as a part of treatment and employment status, respectively. Conclusions. Lebanese women are aware of HRT as a treatment option; however, a lack of both proper information and positive attitude towards HRT use was noted.